Penggunaan Metode Ontology Untuk Perancangan Purwarupa Sistem Smart Home Berbasis Context Aware - Guntur Perdana; Ahmad Ashari (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2019)
Smart home system is a computer-aided system that will provide all comfort, safety, security and energy savings, which works automatically and programmed through a computer in a building or home. One of the method that can be used to design smart home is context aware method. Context aware can work with the help of several other methods such as ontology method. Ontology has a variety of definition and always changes time by time. Ontology method is one of method that can process complex data. The ontology method allows complex reasoning and representation with better results. Constraints that are often encountered when designing a system that looks complex will face many problems such as many ambiguous domains. The existence of an ontology design before carrying out the prototype design of the smart home system will facilitate the smart home design process especially if the system will be made more complex so it would allows ambiguity from multiple domains. Testing with this ontology method is effective enough to minimize ambiguity from each domain, because each domain is designed with different characteristics. The results of the test concluded that the ontology design can be realized as a prototype of the smart home system.